Oil-based formulations containing arthropodpathogenic fungi to control Rhipicephalus microplus - Angelo, Isabele da Costa; Neto, Hilton Carmo Diniz; Santos, Samilla V.; Perinotto, Wendell Marcelo de Souza; Quinelato, Simone; Santos, Huarrisson Azevedo; Gôlo, Patrícia Silva; Camargo, Mariana Guedes; Marciano, Allan Felipe; Bittencourt, Vânia Rita Elias Pinheiro (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Angelo I.C., Diniz-Neto H.C., Santos S.V., Perinotto W.M.S., Quinelato S., Santos H.A., Gôlo P.S., Camargo M.G., Marciano A.F. & Bittencourt V.R.E.P. [Oil-based formulations containing arthropodpathogenic fungi to control Rhipicephalus microplus.] Formulações oleosas contendo fungos artropodopatogênicos para o controle de Rhipicephalus microplus. Revista Brasileira de Medicina Veterinária, 37(Supl.1):18-24, 2015. Departamento de Epidemiologia e Saúde Pública, Universidade Federal Rural do Estado do Rio de Janeiro, BR 465, Km 7, Seropédica, RJ 23897-970, Brasil. E-mail: isabeleangelo@yahoo.com.br Rhipicephalus microplus ticks are responsible for economical losses estimated in U 3.24 billions per year in Brazil. Arthropodpathogenic fungi are an important alternative to the chemical control of this arthropod; however to be efficient in the field, formulations must be developed to protect conidia against environmental stresses. The present study compared the efficacy of mineral or vegetal oil-based formulations containing Metarhizium anisopliae s.l. or Beauveria bassiana s.l. as well as their association to control R. microplus engorged females. M. anisopliae and B. bassiana isolates were cultivated in Potato Dextrose Agar medium and maintained under optimal conditions. Single fungus oil-based formulations were prepared with the following proportions: 84% aqueous fungal suspension; 15% sterile oil; 1% Tween 80. Associated fungal formulations were prepared as follows: 42% aqueous M. anisopliae suspension; 42% aqueous B. bassiana suspension; 15% sterile oil and 1% Tween. Engorged females were immersed in 1 mL oil formulations. The following biological parameters were evaluated: initial weigh of engorged female; weight of egg mass; egg production index; nutritional index and percentage of tick control. There was no difference in the percentage of tick control when M. anisopliae s.l. and/or B. bassiana s.l. were tested in mineral oil. Although, when vegetable oil-based formulations were tested, only M. anisopliae s.l. formulations (both single and associated) had satisfactory control percentage (41.97% and 40. 13%) while single fungus B. bassiana s.l. formulation yield a very low percentage of tick control (10.88%). Accordingly, the use of different oils (mineral or vegetable oils) may affect in different ways the arthropodpathogenic fungi efficacy to control R. microplus. Therefore, different oils should be tested in formulations to control ticks, as well as their interactions with different fungal isolates what will contribute to the development of a promising alternative to control this important parasite.